Enhanced electron acceleration in aligned nanowire arrays irradiated at highly relativistic intensities. (1st November 2019) - Moreau, A; Hollinger, R; Calvi, C; Wang, S; Wang, Y; Capeluto, M G; Rockwood, A; Curtis, A; Kasdorf, S; Shlyaptsev, V N; Kaymak, V; Pukhov, A; et al.
Abstract: We report a significant enhancement in both the energy and the flux of relativistic electrons accelerated by ultra-intense laser pulse irradiation (>1 × 10 21 W cm −2 ) of near solid density aligned CD2 nanowire arrays in comparison to those from solid CD2 foils irradiated with the same laser pulses. Ultrahigh contrast femtosecond laser pulses penetrate deep into the nanowire array creating a large interaction volume. Detailed three dimensional relativistic particle-in-cell simulations show that electrons originating anywhere along the nanowire length are first driven towards the laser to reach a lower density plasma region near the tip of the nanowires, where they are accelerated to the highest energies. Electrons that reach the lower density plasma experience direct laser acceleration up to the dephasing length, where they outrun the laser pulse. This yields an electron beam characterized by a 3× higher electron temperature and an integrated flux 22.4× larger respect to foil targets. Additionally, the generation of >1 MeV photons were observed to increase up to 4.5×.